The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Companion to sexuality studies - Naples, Nancy A. (Wiley-Blackwell companions to sociology, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

Lesbian camp: An unearthing - Nielsen, Elly-Jean (Journal of Lesbian Studies, 2016)
Camp—a sensibility, a style, and a form of artistic selfexpression—is an elusive concept said to be in the eye of the beholder. To refute Susan Sontag’s (1966) claims that camp is apolitical and not especially homosexual, a number of recent scholarly works have been geared toward revealing camp’s fundamental gayness. With the odd footnote aside, lesbian camp has been collapsed into the category of gay male camp, if not eclipsed entirely. Despite the negligible efforts made to legitimize lesbian camp, there are numerous salient cultural examples one might draw on to illustrate, typify, and substantiate a lesbian camp sensibility. I lay the ground work for this scholarly exercise by outlining various definitions and critiques of camp, and by discussing its history and application to queer theory. Then, to unveil lesbian camp, three nonmutually exclusive categories are discussed: classic, erotic, and radical. By gathering various strands of inquiry, and various textual examples (e.g., photography, artistic performances, and literary tropes), this article attempts to reach a more inclusive and nuanced understanding of lesbian camp.
Keywords: approches et analyses; butch/femme; discipline; personnes lesbiennes; psychologie; queer; ressource en ligne; sciences humaines

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (Recherches (Paris. 1994), 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social